Managing Online Classroom for Vocational High School Students: A Self-Observation Report - Setiawan, Amalia Nur Majid (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This research aimed to investigate how to manage online classes in vocational high schools and involve students' contributions during online classes. The subjects of this research were 12th-grade students majoring in hospitality. There were 31 students involved in gathering the data. The method used in this research was a self-observation report. The data were derived through teaching and learning activities and managing online classes, which were carried out synchronously and asynchronously. This study found that online classroom management is important in making teaching and learning activities effective and could make students more involved in synchronous or asynchronous classes.